Overwash hazards assessment using a simplified process based approach - Plomaritis, Theocharis A. (2018)
Coastal communities are threatened by the impact of severe storms that may cause significant loss or damage of property and life. One of the main processes behind such impacts is the overwash of coastal barriers. In order to estimate the losses associated with a particular event, overwash must be properly parameterized. Here, we propose a novel approach to estimate potential overwash hazards, which includes the associated major processes and crucial parameters. For that purpose it was used the parametrisation of the physical processes developed by Donnelly (2008), and the overwash hazard was related to both flow velocity and flow depth, which are in turn a function of lateral spreading of the flow and percolation. The proposed method requires the selection of a validated run-up formula for the study area; a percolation constant for infiltration; a typical value for the run-up lens; and a storm beach profile. Combining these parameters, the overwash depth and velocity for different return periods can be estimated together with the associated hazards. The advantages of the present approach are: adaptability to any environment where overwash processes are important, time efficiency on evaluating overwash hazards, and the assessment of hotspot areas at a regional scale (tens to hundred kilometres).